Surface Microornamentation of Demosponge Sterraster Spicules, Phylogenetic and Paleontological Implications - Cárdenas, Paco (Frontiers in Marine Science, 2020)
Siliceous spicules in demosponges exist in a variety of shapes, some of which look like minute spheres of glass. They are called ‘sterrasters’ when they belong to the Geodiidae family (Tetractinellida order) and ‘selenasters’ when they belong to the Placospongiidae family (Clionaida order). Today, the Geodiidae represent a highly diverse sponge family with more than 340 species, occurring in shallow to deep waters worldwide, except for the Antarctic. The molecular phylogeny of Geodiidae is currently difficult to interpret because we are lacking morphological characters to support most of its clades. To fill this knowledge gap, the surface microornamentations of sterrasters were compared in different genera. Observations with scanning electron microscopy revealed four types of surfaces, which remarkably matched some of the Geodiidae genera: type I characteristic of Geodia, type II characteristic of Pachymatisma, Caminus and some Erylus; type III characteristic of other Erylus; type IV characteristic of Caminella. Two more subtypes were identified in Geodia species: warty versus smooth rosettes. These different microornamentations were mapped on new Geodiidae COI (Folmer fragment) and 28S (C1-C2) phylogenetic trees. The monophyly of the Geodiidae was once again challenged, thereby suggesting that sterrasters have evolved independently at least three times: in the Geodiinae, in the Erylinae and in Caminella. Surface microornamentations were used to review the fossil record of sterrasters and selenasters through the paleontology literature and examination of fossils. It was concluded that ‘rhaxes’ in the literature may represent mixes of sterrasters and selenasters: while Rhaxella spicules may belong to the Placospongiidae, Rhaxelloides spicules belong to the Geodiidae. The putative Geodiidae fossil genera, Geoditesia and Geodiopsis, are reallocated to Tetractinellida incertae sedis. Isolated Miocene-Pliocene fossil sterrasters Hataina Huang, 1967, Silicosphaera Hughes, 1985 and Conciliaspongia Robinson and Haslett, 1995 become junior synonyms of Geodia Lamarck, 1815. Overall, the fossil record suggested that Geodiidae was present at least since the Middle Jurassic (163-166 Mya), while Geodia sterrasters were present since the Santonian/Campanian boundary, Late Cretaceous (83.6 Mya).